Clinical Outcome of Neoadjuvant Radiochemotherapy in Locally Advanced Cervical Cancer: Results of an Open Prospective, Multicenter Phase 2 Study of the North-Eastern German Society of Gynecological Oncology. Issue 3 (March 2017) - Koensgen, Dominique; Sehouli, Jalid; Belau, Antje; Weiss, Martin; Stope, Matthias B.; Großkopf, Vivien; Eichbaum, Michael; Ledwon, Peter; Lichtenegger, Werner; Zygmunt, Marek; Köhler, Günter; Mustea, Alexander
Abstract : Objective: The aim of this study was to determine the response rate, toxicity, operability, and surgical complication rate of neoadjuvant concomitant radiochemotherapy (cRCH) (ifosfamide + carboplatin) followed by radical hysterectomy plus external-beam radiotherapy with curative intention in locally advanced primary inoperable stages IIB and IIIB squamous cell cervical cancer. Methods: Patients with cervical cancer from 8 departments were enrolled. Patients received 3 cycles of ifosfamide 1.2 mg/m 2 (+mesna 20%) plus carboplatin (area under the curve = 4), every 21 days, and concomitant external-beam radiotherapy (50.4 Gy [1.8 Gy/d]). Operability and remission were evaluated by clinical gynecological examination in general anesthesia (magnetic resonance imaging was optional), 4 weeks after the third cycle of cRCH. In case of achieved operability, a radical hysterectomy with pelvic lymphadenectomy was performed within 6 weeks after cRCH. If surgery was not performed because of incomplete remission or patient preferences, vaginal brachytherapy (15 Gy [5 Gy/d]) was given additionally. Results: Forty-four patients were enrolled. Distribution of FIGO (International Federation of Gynecology and Obstetrics) tumor stage was as follows: IIB (19 patients) and IIIB (25 patients). All patients completed cRCH. Grade 3/4 hematologic toxicities (% of all cycles) were moderate: leukopenia, 7.3; thrombocytopenia, 2.4; and anemia, 3.2. In 13.8%, treatment cycles were delayed because of hematologic toxicity. Blood transfusions were given in 17.7% and granulocyte colony-stimulating factor in 39.5%. Overall, grade 3/4 nonhematologic toxicities were seldom (6.5%). Clinical overall response rate was 95.2%. Operability was achieved in 85.7%. Surgery was performed in 83.3%. Pathological response rates were as follows: pathological complete remission, 33.3%; partial remission, 63.3%; stable disease, 3.3%. Conclusions: Our study demonstrates that cRCH is an effective and tolerable regimen in locally advanced cervical cancer treatment.